Ontologi Pendidikan Islam - Fajar Dwi Mukti; Ayu Sholina (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2019)
Ontology is built from the greek roots “Ontos”which means what exists and “Logos” which mens the study. Globally, the term ontology can be interpreted as a study of being and by extension of existence. Ontology studies is the actual state of something, not a temporary state that is always changing. Ontology is an analysis of material objects from science, namely empirical matters that discuss about what you want to know, analyze about the objects studied by science, what is the actual form of the object, how the relationship between these objects with human capture (for example: thinking, feeling and sensing) that produces knowledge.